Stability analysis for a power system with nonlinear voltage controller - Xie, Yuan. (2012)
A power system must be represented as a nonlinear system for large disturbances. Although power system stability may be broadly defined on the basis of different operating conditions, the problem of transient stability is frequently considered. It concerns the continuation of synchronism between generators following a severe disturbance. Voltage quality is another critical factor of power supply in power system operation.